2018
DOI: 10.17305/bjbms.2018.2376
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-466 (miR-466) functions as a tumor suppressor and prognostic factor in colorectal cancer (CRC)

Abstract: MicroRNAs (miRNAs) have an important role in the regulation of tumor development and metastasis. In this study, we investigated the clinical and prognostic value as well as biological function of miR-466 in colorectal cancer (CRC). Tumor and adjacent healthy tissues were obtained from 100 patients diagnosed with CRC. miR-466 expression was determined by quantitative reverse transcription polymerase chain reaction (qRT-PCR). mRNA and protein levels of cyclin D1, apoptosis regulator BAX (BAX), and matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 27 publications
0
51
0
Order By: Relevance
“…3 CRC has been reported to be prevalent in the elderly with an average age of about 71 years old; however, the average age of CRC has been falling in recent years; so the incidence of the disease in people under 50 years are afflicted. 3 CRC has been reported to be prevalent in the elderly with an average age of about 71 years old; however, the average age of CRC has been falling in recent years; so the incidence of the disease in people under 50 years are afflicted.…”
mentioning
confidence: 99%
“…3 CRC has been reported to be prevalent in the elderly with an average age of about 71 years old; however, the average age of CRC has been falling in recent years; so the incidence of the disease in people under 50 years are afflicted. 3 CRC has been reported to be prevalent in the elderly with an average age of about 71 years old; however, the average age of CRC has been falling in recent years; so the incidence of the disease in people under 50 years are afflicted.…”
mentioning
confidence: 99%
“…Twenty-four studies demonstrated the downregulation of twenty-five miRs associated with advanced TNM stage: miR-302c 67 , miR-466 68 , miR-340 69 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-384 74 , miR-199b 48 , miR-128 75 , miR-33b 76 , miR-155-5p 77 , miR-154 78 , miR-149 79 , miR-194 80 , miR-133b 37 , miR-15a 34 , miR-100 81 , miR-133a 41 , miR-335 82 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 and miR-16 34 . Two studies demonstrated the upregulation of miR-182 43, 44 associated with advanced TNM stage and others 22 studies pointed 23 different upregulated miRs associated with advanced TNM stage.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with previous research showing that miR‐181b was involved in transforming growth factor beta‐induced epithelial‐to‐mesenchymal transition and GC metastasis (Zhou et al ., ). Considering protective factors, we noted that miR‐145 could inhibit the malignant phenotypes and suppress metastasis of GC via different molecular mechanisms (Gao et al ., ; Lei et al ., ; Tong et al ., ; Xing et al ., ; Xue et al ., ; Zheng et al ., ). In another study, miR‐7‐3 was confirmed to be an independent prognostic indicator for stomach adenocarcinoma (Huo, ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, miR‐7‐3 was confirmed to be an independent prognostic indicator for stomach adenocarcinoma (Huo, ). Two miRNAs, miR‐466 and miR‐3144, have been indicated as tumor suppressors in other types of cancers (Colden et al ., ; Lin et al ., ; Tong et al ., ), although there are no data available regarding their roles in GC. Other miRNAs, miR‐365a, miR‐3923, miR‐549a, miR‐378i and miR‐4793, are also reported for the first time in GC in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation